Comparison Ability of Polymers Acrycoat S100 And HPMC K4M to Entrapment Efficiency Domperidone in Microspheres - Pratiwi Apridamayanti; Nora Nurlina Sinaga; Rise Desnita (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Domperidone is a prokinetic and antiemetic agent which has low bioavaibility. To increase the bioavaibility of drug, it can be modified into microsphere that can hold drug more longer in gastric to improve the bioavaibility. The microsphere preparation requires a polymer that can make matrix system to protect and deliver the drugs. Acrycoat S100 and HPMC K4M are the usual polymers that used for encapsulation and  have biodegradable characteristic. The aim of this research is to know the comparison ability of two different polymers to entrapment the drug in microsphere. Microsphere domperidone made by solvent evaporation method in 6 formula. F1, F2 and F3 using 50 mg, 100 mg and 150 mg Acrycoat S100 polymer, while F4, F5 and F6 using 50 mg, 100 mg and 150 mg HPMC K4m polymer. The tests were conducted by the determination of the percentage of entrapment efficiency using UV spectrophotometer and evaluation of organoleptic, particle measurement and surface microsphere morphology. The results showed that F3 with Acrycoat S100 polymer has a greater entrapment efficiency of 78,712% ± 4,260% compared to the highest percentage efficiency of HPMC K4M polymer of 4,734±0,390.Key words: Acrycoat S100, domperidone, entrapment efficiency, HPMC K4M, microsphere